CLINICAL AND PATHOGENETIC CHARACTERISTICS OF PEPTIC ULCER OF THE STOMACH AND DUODENUM - Salimova Nigora Bakhodirovna (Journal of Artificial Intelligence and Digital Economy, 2024)
In order to assess the clinical, pathogenetic, functional variant of the course of peptic ulcer disease, I conducted a study of 112 patients with gastric ulcer (34), duodenal ulcer (78). The diagnosis was verified in accordance with the requirements of the modern standard, with an assessment of histomorphological secretory motor, hormonal disorders, as well as the degree of N. rulori contamination, eradication and its effectiveness. Psychosomatic status was assessed using complex methods: multilateral personality studies, the Hamilton scale for assessing depression, the Spielberg scale of situational and personal anxiety, the Beck depression scale, the "unfinished sentences" method for assessing violations in the relationship system.